Stereo-electroencephalography identifies N2 sleep and spindles in human hippocampus. Issue 9 (September 2017) - Carpentier, Nicolas; Cecchin, Thierry; Koessler, Laurent; Louis-Dorr, Valérie; Jonas, Jacques; Vignal, Jean-Pierre; Carpentier, Marc; Szurhaj, William; Bourgin, Patrice; Maillard, Louis
Highlights: The absolute powers of the hippocampal signal are distinct during N2 stage compared to N3 stage. The hippocampal sleep spindles exhibit a frequency closer to fast than slow cortical spindles. The analysis of sleep cycles suggests a homeostatic process within hippocampus. Abstract: Objectives: To describe the hippocampal stereo-electroencephalogram during sleep according to sleep stages (including N2 sleep) and cycles, together with the hippocampal spindles. Methods: All patients with drug-resistant focal epilepsy undergoing intra-hippocampal implantation between August 2012 and June 2013 at Nancy University Hospital were screened. Six patients with explored hippocampus devoid of pathological features were analyzed. During one night, we identified continuous periods of successive N2, N3 and REM sleep for two full cycles. We performed a spectral analysis of the hippocampal signal for each labeled sleep period. Results: N2, N3 and REM sleeps were individualized according to their spectral powers, for each frequency band and sleep cycle. Hippocampal spindles showed dynamic intrinsic properties, the 11.5–16 Hz frequency band being mainly dominant, whereas the 9–11.5 Hz frequency band heightening during the beginning and the end of the transient. For N3 and REM sleep stages, the power of the hippocampal signal was significantly decreased between the first and the second sleep cycle. Conclusion: Distinct N2 sleep, fast spindles and homeostatic profile are all common properties shared by hippocampus and cortex during sleep. Significance: The close functional link between hippocampus and cortex may have various sleep-related substrates.